Stimulating children's moral and religious development: the influence of cute and smart dolls - Heldanita; Bakhtiar, Nurhasanah; Sri Suryanti, Dewi; Murniati, Wahyuni; Mastura; Irawan, Yossy; Sherly Anggriani (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background: Based on the results of observations made at Harapan Ibu Kindergarten, it was found that there was a moral and religious imbalance in childhood. Objective: This study aims to determine the influence of educational toys, namely cute smart dolls, on the moral and religious development aspects of children aged 5-6 years at Harapan Ibu Kindergarten. Method: This study uses a quantitative experimental research method using a pre-experimental research design with one group pretest-posttest with a t-test using the formula thitung > ttabel. The sample consists of 22 children, while the population is all children in the Harapan Ibu Kindergarten environment. Results: The results of the study showed that there was an increase in the moral and religious development of group B children at Harapan Ibu Kindergarten by 87.18%, which is in the high criteria with the normalization formula of acquisition. The results of the t-statistical test obtained a sig value of 0.001 <0.05 with a calculated t value of 51.516 and a t table of 1.725050. Therefore, Ho is rejected and Ha is accepted. Conclusion: Educational game tools in the form of dolls smart funny influential​ to moral and religious development of children aged 5-6 years at Harapan Ibu Kindergarten.